Sustainable freight transport optimisation through synchromodal networks. Issue 1 (1st January 2017) - Agbo, Aaron Agbenyegah; Zhang, Yanwei
Abstract: The conventional intermodal freight transportation system lacks the needed flexibility, efficiency and effectiveness among other things. The search for more sustainable system for maritime-hinterland transportation has culminated in the development of the synchromodality concept. In this study, mathematical model is formulated and used to experiment the feasibility and applicability of the concept of synchromodality in Ghana. Data for the numerical analysis for the given corridor is obtained from online sources and through the direct interview of experts in the field. Coupled with this, expert judgment of the researchers is also used. The results of the optimisation were plotted in a graph using OriginPro 9.0, 32-Bit Software. From the study results, the synchromodal service design yielded a difference of about 22% cost savings compared with the unimodal service due to the usage of fewer of trucks. The waiting penalty at the terminal of origin is also considerably reduced. When compared with the intermodal service, the synchromodal service offered a cost savings of about 8%.The results of this research show that the innovative concept has the potentials of ensuring sustainability, flexibility and cost reduction among other things, in freight transportation sector. The sustainability is obtained through better modal split and parallel use of modes for maritime-hinterland freight transportation. Furthermore, the study reveals that synchromodality has the potentials of increasing transport service utilisation. The benefits of environmental sustainability are achieved through less usage of trucks resulting in a reduction in environmental pollution, road congestion, noise, etc.